Evaluation of Recreational Experience at a Coastal Wetland: A Visitor Survey at Maduganga Estuary, Sri Lanka - Marasinghe, S.S; Perera, P.K.P; Kotagama, S.W. (International Forestry and Environment Symposium, 2019)
With the rising demand for nature-based tourism at coastal environments in Sri Lanka, an in-depth understanding of visitor perceptions is vital in sustainable management of such natural ecosystems. Maduganga estuary is one of the famous nature-based tourism destinations which attracts both local and foreign tourists. There are limited or no published research on the experience and perception of visitors to coastal wetlands of Sri Lanka. Therefore, this study was focused on evaluating visitor motivations, behaviours, attitudes and knowledge on environmental concepts and the level of importance and satisfaction of recreational experience. The visitor experience at the destination was measured with 16 attributes, by using Importance Performance Analysis (IPA). The information was gathered by using a structured questionnaire which was administered via face-to-face interviews with visitors to Maduganga, who are 18 years of age and older. With a response rate of 53.9%, 326 questionnaires were completed during the survey period. The respondents were dominated by the young, well- educated, male visitor segment. According to results, “to be in a natural setting” was the main motivation to be in this location and followed by “to use free time” and “to be with family or friends”. Relaxing / fun / enjoyment, enjoying boat rides and photography were the most popular activities among visitors. Importance Performance Analysis demonstrated that all the attributes related to visitor experience lie within the keep up the good work quadrant. “Feeling safe on the boat” was the attribute which had the highest importance (mean=4.41 in 5 point Likert scale) and “Abundance of wildlife had the lowest importance (mean=3.66). “Number of passengers in the boat” had the highest effect on satisfaction (mean=4.01) while “Guides’ knowledge about the river, flora and fauna” was recorded as the attribute with lowest satisfaction (mean=3.43). Overall results of the study highlight the importance of management/ regulation of recreational activities and maintaining the quality of natural environment to enhance the visitor experience and satisfaction. Potential management implications and visitors’ perception on recreation management are further discussed.
Keywords: Importance, satisfaction, visitor motivations, tourism, boats, natural environment